Environmental impacts of the Houthis’ attacks against commercial shipping in the Red Sea - Oral, Ferhan (Frontiers in Political Science, 2025)
As a result of the Houthis’ attacks against commercial shipping in the Red Sea, shipping companies were compelled to reroute their ships via the Cape route instead of the regular Suez Route, which impacted the environment in addition to fuel prices and transit times. Among the environmental effects were the potential for oil spills from tankers that were attacked, the release of hazardous cargo from sunken cargo ships, and a 30–35% increase in carbon emissions resulting from the additional 3,000 nautical miles traveled. As an example of the first environmental impact, a bulk carrier carrying more than 41,000 tons of fertilizer when it was attacked and subsequently sank, resulting in spillage into the Red Sea, and an oil tanker carrying one million barrels of crude oil, which was later transferred to another tanker and towed to a safe port, can be cited. This study aims to highlight the environmental impacts and risks associated with the Houthis’ attacks in the Red Sea, taking into account the maritime security and geopolitical perspectives through secondary research. The main finding of the study is that maritime security threats and risks can have detrimental effects on the environment, in addition to their financial impacts, and that strengthening organizational mechanisms is crucial.